Relations between bioelectrical muscles activity and Isokinetic strength parameters in 17-19-year-old judoists - Dornowski, M. (Baltic Journal of Health and Physical Activity, 2010)
Background: Muscle strength as an element of preparation and sport competition is one of the most important aspects in technical and tactical efficiency. The aim of this study was to define the level of relation between bioelectrical muscle activity and isokinetic strength parameters in 17-19-year-old judoists.